Perlindungan Hukum Bagi Pemegang Merek Dagang Terdaftar dengan Penerapan Prinsip First To File Terhadap Pihak Lain : Studi Kasus Putusan MA Nomor 161K/Pdt.Sus-HKI/2023 - Wibowo, Sigit (Jurnal Hukum Caraka Justitia, 2023)
This research aims to determine and analyze the form of legal protection for registered trademark holders based on the first-to-file principle against other parties who have bad intentions in the form of resembling the reputation of the registered trademark. The research uses a statutory approach and a case approach related to applying the first-to-file principle for registered brand owners toward parties passing off the registered mark. Like the case of the registered trademark MS Glow in the Supreme Court cassation decision Number: 161K/Pdt.Sus-HKI/2023). The qualitative analysis method is built based on data and substance originating or sourced from various literature, books, journals scientific works, laws, and regulations.The result of this research is the legal protection for the registered trademark holder (MS Glow) to have the right to their trademark and the right to produce their cosmetic brand, and for other parties (PS Glow) to no longer use their brand because the principle of first to use and first to file exists in the owner of the MS Glow trademark. As a legal consequence of the Supreme Court's cassation decision, PS Glow must stop cosmetic products (PS Glow) and withdraw all PS Glow brand products from the cosmetics business. Considering that the result of this decision is a decision at the cassation level, the decision has permanent legal force.